2022
DOI: 10.1080/02656736.2022.2113826
|View full text |Cite
|
Sign up to set email alerts
|

Biological modeling in thermoradiotherapy: present status and ongoing developments toward routine clinical use

Abstract: Biological modeling for anti-cancer treatments using mathematical models can be very supportive in gaining more insight into dynamic processes responsible for cellular response to treatment, and predicting, evaluating and optimizing therapeutic effects of treatment. This review presents an overview of the current status of biological modeling for hyperthermia in combination with radiotherapy (thermoradiotherapy). Various distinct models have been proposed in the literature, with varying complexity; initially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…34 For decades, it has been observed that hyperthermia has a synergistic effect with neoadjuvant chemotherapeutics and radiotherapy in the clinic, improving the treatments. 35,36 Tumor vascular permeability presents one of the important challenges which needs to be overcome to improve drug delivery. Local hyperthermia increases the pore size in tumor vasculature, reduce hydrodynamic burdens, like those stimulated by the intratumoral interstitial fluid flow and pressure which could lead to nanoparticle (∼100 to 150 nm in diameter) extravasation.…”
Section: Complexes' Size and Polydispersity Is Reduced Bymentioning
confidence: 99%
“…34 For decades, it has been observed that hyperthermia has a synergistic effect with neoadjuvant chemotherapeutics and radiotherapy in the clinic, improving the treatments. 35,36 Tumor vascular permeability presents one of the important challenges which needs to be overcome to improve drug delivery. Local hyperthermia increases the pore size in tumor vasculature, reduce hydrodynamic burdens, like those stimulated by the intratumoral interstitial fluid flow and pressure which could lead to nanoparticle (∼100 to 150 nm in diameter) extravasation.…”
Section: Complexes' Size and Polydispersity Is Reduced Bymentioning
confidence: 99%
“…The biological treatment evaluation provides insight into the effect of time interval, which is not accounted for in standard thermal dose evaluation and allows qualitative evaluation of dose heterogeneity and different treatment scenarios with varying time intervals. Future research aims at more advanced models also including other relevant hyperthermia mechanisms [ 19 ]. This challenging task requires carefully designed preclinical experiments to obtain essential modelling parameters as a function of temperature and time interval.…”
Section: Discussionmentioning
confidence: 99%
“…Biological modelling could be very helpful to model dynamic processes responsible for cellular response to treatment, thereby providing more insight into clinical implications of the complex synergy between radiotherapy and hyperthermia [ 19 ]. In radiotherapy, biological modelling is quite common to compare fractionation schemes, or to predict tumor control and normal tissue toxicity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the EVPR models consist of a limited amount of tissues, such as fat, muscle, bone, internal air and tumour. The implemented AI segmentation allows to conduct simulation studies including temperature and thermoradiotherapy modelling with realistic patient 3D models [28][29][30]. These 3D models can be obtained from widely available public repositories, enabling non-clinical groups to also work in this area of research.…”
Section: Discussionmentioning
confidence: 99%